Performance Analysis for RIS-Aided Secure Massive MIMO Systems With Statistical CSI - Ren, Hong; Liu, Xueya; Pan, Cunhua; Peng, Zhangjie; Wang, Jiangzhou (IEEE wireless communications letters, 2023)
This letter studies a reconfigurable intelligent surface (RIS)-aided secure massive multiple-input multiple-output (MIMO) communication system. We derive the approximate expression of the sum achievable security data rate (ASDR) with statistical channel state information (CSI). To further improve the system performance, a genetic algorithm (GA) is proposed to optimize the RIS's phase shifts, where both the continuous and discrete phase shifts are considered. Finally, simulation results confirm the correctness of our derived expressions, and demonstrate the effectiveness of using RIS in improving the security performance.